2018
DOI: 10.1002/ajmg.b.32648
|View full text |Cite
|
Sign up to set email alerts
|

CNKSR1 gene defect can cause syndromic autosomal recessive intellectual disability

Abstract: The advent of high‐throughput sequencing technologies has led to an exponential increase in the identification of novel disease‐causing genes in highly heterogeneous diseases. A novel frameshift mutation in CNKSR1 gene was detected by Next‐Generation Sequencing (NGS) in an Iranian family with syndromic autosomal recessive intellectual disability (ARID). CNKSR1 encodes a connector enhancer of kinase suppressor of Ras 1, which acts as a scaffold component for receptor tyrosine kinase in mitogen‐activated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Cg13690126 is located in CNKSR1 , a protein-coding gene with low tissue expression specificity. Defects in CNKSR1 have been linked to syndromic autosomal recessive intellectual disability (ID) [ 59 , 60 ]. Najmabadi et al [ 61 ] speculate its function as a scaffold protein mediating communication between Ras and Rho GTPase signaling pathways which have in turn been shown to play a role in neurodevelopmental disorders [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cg13690126 is located in CNKSR1 , a protein-coding gene with low tissue expression specificity. Defects in CNKSR1 have been linked to syndromic autosomal recessive intellectual disability (ID) [ 59 , 60 ]. Najmabadi et al [ 61 ] speculate its function as a scaffold protein mediating communication between Ras and Rho GTPase signaling pathways which have in turn been shown to play a role in neurodevelopmental disorders [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASD represents a broad clinical condition including deficits in social communication and interactions, repetitive behaviors, and restrictive interests ( Totsika et al, 2011 ). As well as epilepsy ASD frequently coexists with ID: it is estimated that 40%–70% of ASD individuals suffers also from ID ( Bertrand et al, 2001 ; Chakrabarti and Fombonne, 2001 ; Charman et al, 2011 ; Almuhtaseb et al, 2014 ; Jensen and Girirajan, 2017 ; Kazeminasab et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the UniProt database, CNKSR1 , EPHA2 , CLSPN , OLFML3 , and TARBP1 encode Connector enhancer of kinase suppressor of ras 1, Ephrin type-A receptor 2, Claspin, olfactomedin-like protein, and probable methyltransferase TARBP1, respectively [ 53 ]. Studies have suggested the role of CNKSR1 in brain development [ 54 ], EPHA2 in axon guidance [ 55 ], and CLSPN in cell homeostasis [ 56 ]. OLFML3 has been recognized as a microglia-specific gene whose loss of expression disrupts microglia-associated biological functions [ 57 ].…”
Section: Discussionmentioning
confidence: 99%